EKSPLORASI PROSES BERPIKIR SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA KONTEKSTUAL: STUDI KASUS KELAS X SMA ISLAM AL-ULUM TERPADU MEDAN - Siregar, Ahmad Rifai; Sirait, Agnes Alfi Khairuni; Siahaan, Asrifah; Rahmah, Della Permata; Siregar, Elma Batasia; Nabilah, Khairunnisa'; Khadijah, Mutiara; Matondang, Nur Halimah; Br. Karo, Nur Hidayah (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2024)
The ability to solve contextual mathematical problems is a crucial skill that students need to possess. However, students often encounter difficulties in solving problems presented in real-life contexts. Understanding students' thought processes in solving contextual problems can provide valuable insights for teachers to design more effective learning strategies. This research aims to explore and gain a deep understanding of students' thinking processes when solving contextual mathematical problems, focusing on how students comprehend the problems, the strategies they employ in problem-solving, and the difficulties they encounter during the process. This study will employ a qualitative approach using a case study method, where data will be collected through observations, in-depth interviews, and analysis of students' work. The collected data will be thematically analyzed to identify patterns, strategies, and difficulties experienced by students, with data analysis conducted progressively and iteratively to ensure the depth and validity of findings. The research findings are expected to provide valuable insights into students' thinking processes in solving contextual mathematical problems, which can be utilized by teachers to design more effective learning strategies, assist students in developing problem-solving skills, and enhance students' ability to apply mathematics in everyday life.